Work Environment and Work Motivation on Employee Performance - Ceskakusumadewi Baharuddin; Panus Panus (Advances in Human Resource Management Research, 2025)
Purpose: This study aims to analyze the effects of the work environment and work motivation on employee performance at the Makassar City Transportation Agency, both individually and collectively, as a basis for strengthening human resource management in the public service sector. Research Design and Methodology: This study employs a quantitative, causal design. The study population and sample consist of 92 employees of the Makassar City Transportation Agency, selected using a saturation sampling technique. Data were collected using a questionnaire. Data analysis employed the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach using the SmartPLS software. The evaluation stages included the measurement model (outer model), structural model fit (inner model), and hypothesis testing via the bootstrapping procedure. Findings and Discussion: The results of the study indicate that the work environment and work motivation have a positive and significant effect on employee performance, both individually and collectively. These findings confirm that the interaction between a conducive work environment and strong work motivation shapes civil servant performance. Implications: This study suggests that improving employee performance requires enhancing both the physical and psychosocial aspects of the work environment, as well as strengthening a sustainable system of work motivation to foster greater professionalism among civil servants.